Companion flowering plants enhance the preference and fitness of Trichogramma sp. in biological control - MUHAMMAD USMAN; WILDAN MUHLISON; IRWANTO SUCIPTO; HARI PURNOMO (Society for Indonesian Biodiversity, 2025)
Abstract. Usman M, Muhlison W, Sucipto I, Purnomo H. 2025. Companion flowering plants enhance the preference and fitness of Trichogramma sp. in biological control. Biodiversitas 26: 5671-5678. Trichogramma sp. is a polyphagous egg parasitoid widely applied in biological control of lepidopteran pests. Its performance in the field depends on floral resources that provide nutrition. Flowering plants provide nectar, pollen, and odor that influence the behavior of parasitoids. Identifying compatible flowering plants will be essential for enhancing the efficacy of Trichogramma sp. This study aims to determine the preferences and fitness of Trichogramma sp. on eight flowering plants: Tagetes erecta, Arachis pintoi, Wedelia trilobita, Melampodium divaricatum, Lantana camara, Zinnia peruviana, Turnera subulata, and Turnera ulmifolia. The tests included an olfactory test using a Y-tube olfactometer and analyzed with a chi-square test, and a test of the effect of flowering plants on the fitness of Trichogramma sp. imagoes, analyzed with ANOVA. The olfactory test showed that Trichogramma sp. preferred A. pintoi, T. ulmifolia, and T. subulata. T. subulata can increase the longevity of males and females by 2.4 and 2.3 times, respectively. In contrast, T. ulmifolia can increase the longevity of males by 2.4 times and females by 1.8 times compared to the negative control. Both species can also increase total fecundity and imago emergence. These findings indicate that T. subulata and T. ulmifolia are promising flowering plants for improving Trichogramma sp. performance and can be used as companion plants in sustainable integrated pest management (IPM) systems, strengthening the conservation of natural enemies and supporting long-term pest control strategies.